Component level modelling of heat transfer during vapour phase soldering with finite difference ADI approach. (January 2019) - Bozsóki, István; Géczy, Attila; Illés, Balázs
Highlights: An FDM model with ADI approach was developed for the heating of components in VPS. Heat transfer coefficient was determined and validated in an experimental system. Observed temperature differences (∼100 °C) are significant in component structures. Structural features result in uneven temperature distribution along terminations. Both previous findings affect soldering quality and reliability of the assembly. Abstract: In this paper, the complex heat transfer process of the vapour phase soldering has been investigated on the level of electronic components. VPS is gaining increased attention lately, and the process needs alternative approaches in modelling, compared to conventional soldering processes in electronics mass manufacturing. Component level modelling was not studied deeply in the literature before, so our focus pointed to heat transfer on large size surface mounted electronic components. Applying the Fourier type heat conduction equation, a detailed 3D thermal model of a polyester capacitor on a printed circuit board was implemented, based on X-ray images of an actual assembly. Our model incorporates inner geometry, material inhomogeneity, composite materials and anisotropic thermal conductivity as important thermal features. Transient heating was calculated with Finite Difference Method combining an alternating direction implicit (ADI) approach, using averaged heat transfer coefficient. Validation measurements were performed in our experimental VPS system. The measured data show good agreement with the calculation results and points to possible application for use in advanced engineering and manufacturing environment.